Early Marriage Problems in Indonesia - Angkasa, Aghnat Bintang (Semarang State University Undergraduate Law and Society Review, 2021)
Marriage in Indonesia is based or regulated in Act No. 1 of 1974 concerning Marriage. In Chapter 2, article 7, paragraph 1 reads "Marriage is only permitted if the man has reached the age of 19 (nineteen) years and the woman has reached the age of 16 (sixteen) years". In this paper I will discuss about marriage at a young age or what we are familiar with the term early marriage. The main factor of early marriage is the role of parents in family communication. In this study it is hoped that the community in particular the parents (family) can increase the support and care for the teenagers to be better in the future.